SISTEM INFORMASI MONITORING PROGRES PELAKSANAAN PROYEK (P3) (Studi Kasus : Dinas Bina Marga Provinsi Riau) - Zarnelly Zarnelly (Seminar Nasional Teknologi Informasi Komunikasi dan Industri, 2015)
Dinas Bina Marga of Riau Province is a governmental organization dedicated to the development and improvement of ongoing projects and maintenance of transportation roads and bridges. The problems is Dinas Bina Marga difficulty to control / monitoring on a weekly , and reports are often too late and cannot easily be seen what problems occurred in the implementation of projects, and led to the slow completion of problems. Based on these problems is a computerized system that can be used as consideration in the decision-making process, the control and monitoring of the project proposed. The indicators in the monitoring of time, scope and cost of use. The system is connected to the object-oriented concepts and design of the system is described using UML. The design of the system is implemented in a web environment based on PHP and MySQL database. And to inform the final system monitoring progress of project implementation Department of Highways Riau Province.Keywords : Information Systems, Monitoring, Project Implementation Progress, UML, Web.